Assessment of the effect of defects on mechanical properties of adhesive bonded joints by using non destructive methods. (15th April 2016) - Tamborrino, Rosanna; Palumbo, Davide; Galietti, Umberto; Aversa, Patrizia; Chiozzi, Samanta; Luprano, Vincenza Anna Maria
Abstract: Mechanical performance of the adhesive joints depends on many parameters including width, depth and continuity of the adhesive layer applied. In this work, lock-in thermography and ultrasound methods were used to detect the dimension of defects of adhesive joints while tensile tests were carried out to assess their strength and stiffness. Both the effect of bond defects and the possibility to use non destructive method for the prediction of strength and stiffness of joints have been discussed considering a statistical analysis of data. Models, useful for predicting mechanical behavior of joints on the basis of their defects, have been developed.